Hunger pains life inside foodbank Britain - Garthwaite, Kayleigh ca. 20./21. Jh (Policy Press, 2023)
In the years since the UK Government embarked on its harsh austerity programme, food poverty has become a major issue, and food banks have been forced into a major role in the lives of countless citizens. This book is built on hundreds of hours of interviews with the people who rely on food banks today, as well as with the volunteers who keep them running on tight budgets and in difficult conditions